Project report on Milton Keynes - College of Aeronautics, Transport Short Course (College of Aeronautics, 1969)
Introduction 1.1.1 This is a project report written by the members of the College of Aeronautics short course held between 24th February and 7th March, 1969. 1.1.2 An Interim Report was presented by the Planning Consultants to the Milton Keynes Development Corporation in December 1968„ The report is not a definitive plan for building the City, but it has been prepared through a process of consultations between the Consultants, the Corporation members and staff, and many of the authorities and departments in central and local government who will be responsible for various aspects of the City. The report can be taken as representing the strategic approach of the Corporation towards the now City at this stage of the planning process, but it is not intended to submit proposals for approval by central and local governments until the complete plan is produced at the end of 1969. 1.1.3 The Interim Report has been published at this stage partly to enable limited development work to be started in advance of the Plan, and partly to encourage discussion by the public and organisations and authorities concerned. It is recognised that new views and further examination may make practicable changes desirable and necessary.